Using Self-regulation to Successfully Overcome the Negotiation Disadvantage of Low Power - Jäger, Andreas; Loschelder, David D.; Friese, Malte (Frontiers in Psychology, 2017)
A plethora of studies has demonstrated that low-power negotiators attain lower outcomes compared to high-power negotiators. We argue that this low-power disadvantage can be conceptualized as impaired goal attainment and that self-regulation can help to overcome it. Three experiments tested this assertion. In Study 1, low-power negotiators attained lower profits compared to their high-power opponents in a face-to-face negotiation. Negotiators who set themselves goals and those who additionally formed if-then plans prior to the negotiation overcame the low-power disadvantage. Studies 2 and 3 replicated these effects in computer-mediated negotiations: Low-power negotiators conceded more than high-power negotiators. Again, setting goals and forming additional if-then plans helped to counter the power disadvantage. Process analyses revealed that negotiators’ concession-making at the start of the negotiation mediated both the low-power disadvantage and the beneficial effects of self-regulation. The present findings show how the low-power disadvantage unfolds in negotiations and how self-regulatory techniques can help to overcome it.